In search of greatness : Russia's communications with Africa and the world - Eribo, Festus, 1950- (Civic discourse for the third millennium., 2001)
An analysis of Russia's foray into communication with Africa and the world. It examines news reports and civic discourse, and explores the intellectual, social, cultural, political, geographical and historical aspects of the relationship between Africa and Russia.